2014
DOI: 10.1177/1088868314535988
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Link Between Impulsivity and Suicidal Behavior

Abstract: It is widely accepted that suicidal behavior often occurs with little planning. We propose, however, that suicidal behavior is rarely if ever impulsive-that it is too frightening and physically distressing to engage in without forethought-and that suicidal behavior in impulsive individuals is accounted for by painful and fearsome behaviors capable of enhancing their capacity for suicide. We conducted a meta-analysis of the association between trait impulsivity and suicidal behavior and a critical review of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
173
3
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(195 citation statements)
references
References 183 publications
12
173
3
7
Order By: Relevance
“…Future research may also explore other dimensions of impulsivity including negative urgency, lack of premeditation, and lack of perseverance (Valderrama et al, 2016). We concur with suggestions that measures of episodic impulsivity be developed (Anestis et al, 2014), and further, that the interaction between trait impulsivity and specific contexts be considered (Mischel and Shoda, 1995). For instance, it would be useful to incorporate an analysis of the effects of specific psychological states during the time of assessment when examining performance on trait impulsivity measures (Glicksohn et al, 2016).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Future research may also explore other dimensions of impulsivity including negative urgency, lack of premeditation, and lack of perseverance (Valderrama et al, 2016). We concur with suggestions that measures of episodic impulsivity be developed (Anestis et al, 2014), and further, that the interaction between trait impulsivity and specific contexts be considered (Mischel and Shoda, 1995). For instance, it would be useful to incorporate an analysis of the effects of specific psychological states during the time of assessment when examining performance on trait impulsivity measures (Glicksohn et al, 2016).…”
Section: Discussionsupporting
confidence: 68%
“…A notable body of research has found evidence of a direct impulsivity-suicide attempt link (e.g., Brodsky et al, 2001;Doihara et al, 2012), while other studies have found no such evidence (e.g., Carli et al, 2010;Grunebaum et al, 2005;Oquendo et al, 2000). Most recently, a meta-analysis (Anestis et al, 2014) comparing individuals with and without histories of suicide attempts indicated that the relationship between impulsivity and suicide attempt history was small (Hedges g =.34). Findings on impulsivity among individuals with multiple versus single attempts is also mixed with some evidence for higher impulsivity among those with multiple attempts (e.g., Bulik et al, 2008;Dougherty et al, 2004a;Maloney et al, 2009), and other research finding no impulsivity differences between these groups (e.g., Brodsky et al, 2001;Iancu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Suicide risk increases in people with mental disorders or impulsive behavior, those facing stressful situations or with easy access to harmful tools such as poisoning, hanging and firearms 17 . Besides that, suicide is three times more common in men than women 18 . Suicide is a prominent risk in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Although impulsivity is clearly related with making more suicide attempts, its role in the severity of the attempts is less clear (Soloff et al 2005 ). The impulsivity of the attempt does not correlate well with the impulsivity of the attempter, and some authors argue that impulsivity as a trait facilitate the exposition to adverse experiences through the lifetime that eventually lead to SB (Anestis et al 2014 ). In fact, aggressiveness has shown to be a better predictor of SB than impulsivity or hostility among depressed patients (Keilp et al 2006 ).…”
Section: Impulsive Aggressionmentioning
confidence: 97%